THE ANALYSIS OF INFLUENCE STATE EXPENDITURES, ISLAMIC BANKING FINANCE AND FOREIGN INVESTMENT (PMA) ECONOMIC GROWTH IN INDONESIA 2017-2022 - Nabilah Al Madani; Dahruji Dahruji (LISAN AL-HAL: Jurnal Pengembangan Pemikiran dan Kebudayaan, 2022)
The purpose of this research were assessing the effect of the correlation between state spending, Islamic banking finance and foreign investment (PMA) economic growth in Indonesia. The research sources of data were secondary data from 2017-2021. From this analysis, the Gross Domestic Product at constant prices was used to measure Indonesia's economic growth. This study were included in quantitative research and applies the Multiple Linear Regression Method. The results of the study based on the t-test (partial test) found that Islamic banking finance and foreign investment (PMA) significantly affect economic growth in Indonesia. Then for the variable State Expenditure did not significantly affect Economic Growth in Indonesia.